2002
DOI: 10.1101/gad.221702
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis PILZ group genes encode tubulin-folding cofactor orthologs required for cell division but not cell growth

Abstract: Plant microtubules are organized into specific cell cycle-dependent arrays that have been implicated in diverse cellular processes, including cell division and organized cell expansion. Mutations in four Arabidopsis genes collectively called the PILZ group result in lethal embryos that consist of one or a few grossly enlarged cells. The mutant embryos lack microtubules but not actin filaments. Whereas the cytokinesis-specific syntaxin KNOLLE is not localized properly, trafficking of the putative auxin efflux c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
131
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 60 publications
5
131
1
Order By: Relevance
“…Particularly, mutational analyses have led to the identification of proteins important for cytokinesis, many of which are conserved among eukaryotes [10,11]. Inactivation of a number of factors that regulate fundamental aspects of MT dynamics certainly leads to the eventual failure in cytokinesis [12]. However, there are factors that act specifically on phragmoplast MTs and regulate the rise and fall of the phragmoplast MT array [13].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, mutational analyses have led to the identification of proteins important for cytokinesis, many of which are conserved among eukaryotes [10,11]. Inactivation of a number of factors that regulate fundamental aspects of MT dynamics certainly leads to the eventual failure in cytokinesis [12]. However, there are factors that act specifically on phragmoplast MTs and regulate the rise and fall of the phragmoplast MT array [13].…”
Section: Introductionmentioning
confidence: 99%
“…TBCC is an essential and key player required for the formation of the tubulin heterodimers by promoting the assembly of the a-and b-tubulin peptides. A study on POR gene in Arabidopsis thaliana showed that it encodes an ortholog of TBCC and plays an important role in releasing competent polymerizable heterodimers (17,18). Conversely, there are no data in the literature about the relationship between TBCC and the cell cycle or response to anti-microtubule agents in breast cancer cells.…”
Section: Introductionmentioning
confidence: 95%
“…This tubulin garage folds the a-and b-tubulin polypeptides and facilitates a/b-tubulin heterodimer formation in the presence of GTP (Steinborn et al, 2002). Both a-and b-tubulin have GTP-binding sites where the a-tubulin site traps the nucleotide within the heterodimer (Spiegelman et al, 1977).…”
Section: Microtubule Structure and Compositionmentioning
confidence: 99%